D-Serine: A Cross Species Review of Safety - Meftah, Amir; Hasegawa, Hiroshi; Kantrowitz, Joshua T. (Frontiers in Psychiatry, 2021)
Background: D-Serine, a direct, full agonist at the D-serine/glycine modulatory site of the N-methyl-D-aspartate-type glutamate receptors (NMDAR), has been assessed as a treatment for multiple psychiatric and neurological conditions. Based on studies in rats, concerns of nephrotoxicity have limited D-serine research, particularly in high dose research. A review of D-serine’s safety is timely and pertinent, as D-serine remains under active study for schizophrenia, both directly (R61 MH116093) and indirectly through D-amino acid oxidase (DAAO) inhibitors. The principal focus is on nephrotoxicity, but safety in other physiologic and pathophysiologic systems are also reviewed. Methods: Using the search terms “D-serine,” “D-serine and schizophrenia,” “D-serine and safety,” “D-serine and nephrotoxicity” in PubMed, we conducted a systematic review on D-serine safety. D-serine physiology, dose-response and efficacy in clinical studies and DAAO inhibitor safety is also discussed. Results: When D-serine doses >500 mg/kg are used in rats, nephrotoxicity, manifesting as an acute tubular necrosis syndrome, seen within hours of administration is highly common, if not universal. In other species, however, D-serine induced nephrotoxicity has not been reported, even in other rodent species such as mice and rabbits. Even in rats, D-serine related toxicity is dose dependent and reversible; and does not appear to be present in rats at doses producing an acute Cmax of less than 2000 nmol/mL. For comparison, the Cmax of D-serine 120 mg/kg, the highest dose tested in humans, is approximately 500 nmol/mL in acute dosing. Across all published human studies, only one subject has been reported to have abnormal renal values related to D-serine treatment. This abnormality did not clearly map on to the acute tubular necrosis syndrome seen in rats, and fully resolved within a few days of stopping treatment. DAAO inhibitors may be nephroprotective. D-Serine may have a physiologic role in metabolic, extra-pyramidal, cardiac and other systems, but no other clinically significant safety concerns are revealed in the literature. Conclusions: Even before considering human to rat differences in renal physiology, using current FDA guided monitoring paradigms, D-serine appears safe at currently studied maximal doses, with potential safety in combination with DAAO inhibitors.